Tariff Volatility and Tariff Policy in Developed and Developing Countries - Sèna Kimm Gnangnon (ZBW - Leibniz Information Centre for Economics, 2020)
In this paper, we investigate 'at the aggregate level', the effect of tariff volatility on tariff rates, using three groups of products, including 'all products', 'manufactured products' and 'primary products', and a large panel dataset covering 163 countries over the period 1995-2017. Results, based on the feasible generalized least squares estimator, have shown for the full sample that tariff volatility leads to a greater extent of tariff liberalization. This finding holds for each of the three groups of products highlighted above, as well as for three sub-samples, including lower-middle income countries, upper-middle income countries and high-income countries. However, for Low-income countries, tariff volatility influences significantly (although negatively) tariff rates only for primary products. Additionally, for recipient-countries of Aid for Trade related to trade policy and regulation (AfTPOL), the effect of tariff volatility on tariff rates is conditional upon the amounts of AfTPOL flows only for primary products. Specially, there exists a substitutability between tariff volatility and AfTPOL flows in influencing tariffs applied on primary products. For lower amounts of AfTPOL flows, tariff volatility induces a greater extent of tariff liberalization, while for higher amounts of these aid flows, tariff volatility results in higher tariff rates. Alternatively, the higher the amounts of AfTPOL flows, the greater is the positive effect of tariff volatility on the extent of liberalization of tariff on primary products.
Keywords: F14; F35; 330; Tariffs; Tariff volatility; Primary products; Manufactured products